Implementasi Metode Pembelajaran Aktif dalam Meningkatkan Keterlibatan Siswa pada Mata Pelajaran Pendidikan Agama Islam - Atiqah Yesi Duanasari; Nadilla Dwi Putri; Gusmaneli Gusmaneli (Politeknik Kampar, 2024)
In learning, there are components related to the learning process, one of which is the learning method. In connection with the learning process under study, it was found that so far the learning material at SMP IT Al-Kahfi was taught through relatively conventional methods, so that the absorption of material for some students seemed monotonous and boring. This study aims to describe the learning methods applied at SMP IT Al-Kahfi. The research method uses descriptive qualitative methods with primary data collection through interviews and observations As for secondary data obtained through documentation. The results showed that the application of active learning methods at SMP IT Al-Kahfi was 100% unsuccessful, this was indicated by the results of observations and interviews with PAI teachers at SMP IT Al-Kahfi. This is also influenced by 2 factors, namely supporting factors such as the existence of adequate learning facilities and resources, high student interest in learning, and the enthusiasm and professionalism of Islamic education teachers in guiding their students and inhibiting factors, namely the existence of some students who are still reluctant to express their opinions, and different student backgrounds. Active learning methods need to be improved so that students can be actively involved in learning activities.